Average and marginal effective tax rates facing workers in the EU: A micro-level analysis of levels, distributions and driving factors - Herwig Immervoll (University of Essex, Institute for Social and Economic Research (ISER), 2004)
Macro-based effective tax rate (ETR) measures do not provide information on the level or distribution of marginal effective tax rates thought to influence household behaviour. They also do not capture differences in average ETRs facing different population sub-groups. I use EUROMOD, an EU-wide tax-benefit model, to derive distributions of average and marginal ETR measures for fourteen countries. Results for each country show how many and which types of individuals face different ETR levels. I consider effective tax burdens on labour income as well as the marginal tax rates faced by working men and women. Results are broken down to isolate the influence of income taxes, social contributions and various types of social benefits.
Keywords: H22; D31; C81; 330; Effective Tax Rates; European Union; Microsimulation